Nitrate reduction of brines from water desalination plants by membrane electrolysis - Bosko, María Laura (2013)
The disposal of the saline effluent generated during membrane water desalination by electrodialysis (ED) or reverse osmosis (RO) is an increasing problem worldwide, especially for the desalination of inland brackish water. Electrolysis can be an alternative to the denitrification of brines by the reduction of nitrates to the desired product (N2). Nevertheless, in a paired electrolysis cell the reduced products could be re-oxidized in the anode by the reverse reactions; for example, nitrite could be again converted to nitrate. Membrane electrolysis can avoid these reactions. The aim of this study was to assess the efficacy of the membrane electrolysis technique in the reduction of nitrate in water. The experiments were performed in an electrochemical cell with two compartments separated by a cation-exchange membrane, the cathode being made of copper and the anode of titanium oxide and ruthenium oxide (70TiO2/30RuO2). Nitrite, ammonium and nitrogen containing gases (most of them N2) were the reaction products. The best value was achieved with a cell voltage of 9 V and an initial concentration of 526 mg/L of NO3−. Under these conditions, high conversion to nitrite and gaseous compounds was registered with the formation of just 7.8 mg/L of ammonium.